Join the conversation on IDNLearn.com and get the answers you seek from experts. Our platform is designed to provide trustworthy and thorough answers to any questions you may have.

Evaluate the following expressions given [tex]h(x) = x^2 + 1[/tex]:

[tex]\[
\begin{array}{l}
(h+k)(2)=\square \\
(h-k)(3)=\square
\end{array}
\][/tex]

Evaluate:

[tex]\[3h(2) + 2k(3) = \square\][/tex]


Sagot :

Let's evaluate the given expressions step-by-step:

### 1. Define and evaluate the functions [tex]\( h(x) \)[/tex] and [tex]\( k(x) \)[/tex]:

Given function [tex]\( h(x) \)[/tex]:
[tex]\[ h(x) = x^2 + 1 \][/tex]

Let's evaluate [tex]\( h(2) \)[/tex]:
[tex]\[ h(2) = 2^2 + 1 = 4 + 1 = 5 \][/tex]

Given function [tex]\( k(x) \)[/tex]:
[tex]\[ k(x) = x + 1 \][/tex]

Let's evaluate [tex]\( k(2) \)[/tex]:
[tex]\[ k(2) = 2 + 1 = 3 \][/tex]

Let's evaluate [tex]\( k(3) \)[/tex]:
[tex]\[ k(3) = 3 + 1 = 4 \][/tex]

### 2. Compute [tex]\((h + k)(2)\)[/tex]:

[tex]\[ (h + k)(2) = h(2) + k(2) = 5 + 3 = 8 \][/tex]

### 3. Compute [tex]\((h - k)(3)\)[/tex]:

[tex]\[ (h - k)(3) = h(3) - k(3) \][/tex]

Let's first find [tex]\( h(3) \)[/tex]:
[tex]\[ h(3) = 3^2 + 1 = 9 + 1 = 10 \][/tex]

Now calculate [tex]\((h - k)(3)\)[/tex]:
[tex]\[ (h - k)(3) = h(3) - k(3) = 10 - 4 = 6 \][/tex]

### 4. Evaluate the expression [tex]\( 3h(2) + 2k(3) \)[/tex]:

Now, using the previously computed values:
[tex]\[ 3h(2) + 2k(3) = 3 \times 5 + 2 \times 4 \][/tex]
[tex]\[ 3h(2) + 2k(3) = 15 + 8 = 23 \][/tex]

### Final Results:
[tex]\[ \begin{array}{l} (h+k)(2) = 8 \\ (h-k)(3) = 6 \\ 3h(2) + 2k(3) = 23 \end{array} \][/tex]

Thus, the values are:
[tex]\[ \boxed{8} \boxed{6} \boxed{23} \][/tex]